2001
DOI: 10.1128/iai.69.3.1488-1491.2001
|View full text |Cite
|
Sign up to set email alerts
|

DsrA-Deficient Mutant of Haemophilus ducreyi Is Impaired in Its Ability To Infect Human Volunteers

Abstract: Haemophilus ducreyi produces an outer membrane protein called DsrA, which is required for serum resistance. An isogenic dsrA mutant, FX517, was constructed previously in H. ducreyi 35000. Compared to its parent, FX517 cannot survive in normal human serum. When complemented in trans with a plasmid containing dsrA, FX517 is converted to a serum-resistant phenotype (C. Elkins, K. J. Morrow, Jr., and B. Olsen, Infect. Immun. 68:1608-1619, 2000). To test whether dsrA was transcribed in vivo, we successfully amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 42 publications
1
61
0
Order By: Relevance
“…However, subsequent testing in the human challenge model for experimental chancroid (for a review, see reference 31) revealed that only a few of these gene products are truly essential for full virulence of H. ducreyi. Mutations in pal (21), hgbA (1), dsrA (8), the flp gene cluster (55), ncaA (22), and lspA1 and lspA2 (29) attenuated the virulence of H. ducreyi in human volunteers, whereas mutations in four other genes caused partial attenuation (4,6,28,34).…”
mentioning
confidence: 99%
“…However, subsequent testing in the human challenge model for experimental chancroid (for a review, see reference 31) revealed that only a few of these gene products are truly essential for full virulence of H. ducreyi. Mutations in pal (21), hgbA (1), dsrA (8), the flp gene cluster (55), ncaA (22), and lspA1 and lspA2 (29) attenuated the virulence of H. ducreyi in human volunteers, whereas mutations in four other genes caused partial attenuation (4,6,28,34).…”
mentioning
confidence: 99%
“…B-451, p. 233, 1996), a copper-zinc superoxide dismutase (42), and a very large protein detected in H. ducreyi culture supernatant fluid (54). To date, isogenic mutants lacking expression of the peptidoglycan-associated lipoprotein (19), the hemoglobin-binding outer membrane protein HgbA (7), and the DsrA outer membrane protein (11) have been shown to exhibit reduced virulence in the human challenge model for experimental chancroid.…”
mentioning
confidence: 99%
“…To date, however, only three outer membrane antigens have been shown to be essential to the ability of H. ducreyi to produce an infection in human volunteers. These include the peptidoglycan-associated lipoprotein (23), the hemoglobinbinding outer membrane protein HgbA (6), and the DsrA protein, which is involved in serum resistance (12,20).…”
mentioning
confidence: 99%